Studi Literatur Evaluatif : Strategi dan Tantangan Pembelajaran IPA di Sekolah Dasar - Della Nanda Sidabalok; Khoirunnisa Nasution; Devi Triana Purba; Syahrial Syahrial (Politeknik Kampar, 2025)
Evaluation in the learning process plays a crucial role, especially in the subject of Natural Sciences (IPA) at the elementary school level. The function of evaluation is not limited to measuring students' learning outcomes, but also serves as a basis for teachers to reflect on and improve the quality of teaching. This study is a literature review with an evaluative approach aimed at examining various evaluation strategies used in science education and identifying the challenges faced in their implementation. Based on the review of various academic references, it was found that effective evaluation approaches include authentic assessment, learning projects, and assessments that emphasize critical thinking skills. Authentic assessment has proven capable of providing a comprehensive picture of student development, encompassing cognitive, affective, and psychomotor aspects. However, the implementation of this evaluation model often faces challenges such as limited facilities, insufficient professional training for teachers, and difficulties in objectively assessing attitudes and skills. Therefore, improving teachers' competencies through training programs and providing adequate resources becomes a strategic step that needs to be taken. The results of this study recommend the importance of strengthening support for teachers in order to realize a valid evaluation system that aligns with the characteristics and needs of elementary school students today.